Pipelined SHA-3 implementations on FPGA: Architecture and performance analysis - Michail, Harris; Ioannou, Lenos; Voyiatzis, Artemios G. (My University, 2015)
.Efficient and high-throughput designs of hash functions will be in great demand in the next few years, given that every IPv6 data packet is expected to be handled with some kind of security features. In this paper, pipelined implementations of the new SHA- 3 hash standard on FPGAs are presented and compared aiming to map the design space and the choice of the number of pipeline stages. The proposed designs support all the four SHA-3 modes of operation. They also support processing of multiple messages each comprising multiple blocks. Designs for up to a four-stage pipeline are presented for three generations of FPGAs and the performance of the implementations is analyzed and compared in terms of the throughput/area metric. Several pipeline designs are explored in order to determine the one that achieves the best throughput/area performance. The results indicate that the FPGA technology characteristics must also be considered when choosing an efficient pipeline depth. Our designs perform better compared to the existing literature due to the extended optimization effort on the synthesis tool and the efficient design of multiblock message processing.
Keywords: Cryptography; FPGA; Hash function; Pipeline; Security